Construction of a stable expression system for endoglucanase in Bacillus subtilis 168M - Minh, Phan Thị Tuyết; Việt, Nguyễn Quốc; Thoa, Nguyễn Kim; Hy, Lê Gia; Mấn, Trần Đình (Vietnam Journal of Biotechnology, 2016)
Beta-D-1,4-endoglucanase plays an important role in biomass hydrolysis, the microorganisms in nature can synthesize this enzyme at very low activity. Together with development of biotechnology, a low enzymatic activity problem has been overcome by using the recombinant method. Several expression systems for β-D-1,4-endoglucanase were designed for use of different cell lines. In this paper, we have constructed a stable expression system for β-D-1,4-endoglucanase gene in Bacillus subtilis 168M. Three main components including the promoter (180 bp) of α–amylase gene from the host strain B. subtilis 168M, the whole open reading frame of β-D-1,4-endoglucanase (1,500 bp) gene from B. amyloliquefacient VLSH08 strain, and the terminator (81 bp) of α–amylase gene from B. licheniformis 3BT2 strain, were reconstructed via megaprimer method. Subsequently, this new reconstitution was ligated into a modified pHT43 vector which was cleaved its own promoter and signal peptide fragment (AmyQ) and transformed into the compotent B. subtilis 168M. The recombinant B. subtilis 168M carrying pHT43[Bspr.endo.Blter] vector showed β-D-1,4-endoglucanase activity at 7 U/ml, 23 times higher than that of the wild type B. amyloliquefacient VLSH08 strain. The successful design and expression of the expression system β-D-1,4-endoglucanase isolated from B. amyloliquefacient strain VLSH08 in pHT43 vector carrying the promoter of the α- amylase gene from B. subtilis strain 168M and the terminator of the α-amylase gene from B. licheniformis strain 3BT2, actively contribute effectively expression of β-D-1,4-endoglucanase for use.